2014
DOI: 10.1016/j.neubiorev.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The Ultimatum Game and the brain: A meta-analysis of neuroimaging studies

Abstract: Social decision-making tasks involve psychological processes key to effective functioning in a complex, social world. The Ultimatum Game (UG) is a widely studied social decision-making task, which models responses to fairness. A number of neuroimaging studies have investigated the UG to identify neural correlates of unfairness and decisions to reject versus accept an offer. We present the first quantitative summary of neuroimaging studies in social decision-making with a meta-analysis of 11 fMRI studies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
134
3
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 48 publications
17
134
3
2
Order By: Relevance
“…This contrast revealed a cluster that extended over a large portion of the mPFC (Figure 2), including both the DMPFC (areas 8 and 9) and VMPFC (area 32), in the same region as recently identified within a meta‐analysis of UG studies (Feng et al., 2015; Gabay et al., 2014). This large cluster survived whole brain cluster correction ( p <  0.001 uncorrected voxel‐wise; p  <   0.05 FWE cluster‐correction) at the level recommended in recent analyses of corrections for multiple comparisons (Eklund et al., 2016; Woo et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This contrast revealed a cluster that extended over a large portion of the mPFC (Figure 2), including both the DMPFC (areas 8 and 9) and VMPFC (area 32), in the same region as recently identified within a meta‐analysis of UG studies (Feng et al., 2015; Gabay et al., 2014). This large cluster survived whole brain cluster correction ( p <  0.001 uncorrected voxel‐wise; p  <   0.05 FWE cluster‐correction) at the level recommended in recent analyses of corrections for multiple comparisons (Eklund et al., 2016; Woo et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Recent meta‐analyses have highlighted that the DMPFC and the Insula are key regions that respond differentially to equitable and inequitable offers in the UG (Feng et al., 2015; Gabay et al., 2014). Similarly, a large number of different paradigms have shown that several regions including both the DMPFC and VMPFC respond to ingroup and outgroup members differently (Cikara & Van Bavel, 2014; Cikara et al., 2014; Harris & Fiske, 2006; Hein et al., 2010; Molenberghs et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations